Primary testicular natural killer/T-cell lymphoma: A CARE-case report and review of literature. Issue 12 (March 2018) - Zhang, Wan-Lin; Ma, Shuang; Jug, Rachel; Li, Fan; Wang, Endi; Zhao, Huan-Yu; Xu, Hong-Tao; Cai, Lin; Yu, Cheng-Qian; Shen, Shuai; Yang, Lian-He
Abstract: Rationale: Primary testicular natural killer (NK)/T-cell lymphoma is an extremely rare and highly aggressive lymphoid malignancy. At present, only 20 cases have been reported. Patient concerns: A 32-year-old Chinese man complained of discomfort and swelling of his right testicle for 3 months. Physical examination revealed a 10 × 10 × 9.5 cm mass on the right side of the scrotum area. Diagnoses: Pathologic evaluation showed effacement of normal testicular parenchymal architecture by small-to-medium-sized lymphoid cells with irregular nuclear profiles, and immunohistochemical studies positively expressed CD2, CD56, cytoplasmic CD3, granzyme B, perforin, and TIA-1. Therefore, the patient was diagnosed with primary testicular NK/T-cell lymphoma. Interventions: The patient underwent CHOP (cyclophosphamide (CTX), pirarubicin (THP-ADM), vincristine (VCR), and prednisolone (PDN)) chemotherapy. Outcomes: The patient relapsed 5 months after his initial presentation and died after an infection and gastrointestinal bleed. Lessons: Clinicopathological assessment of this rare case highlights the clinical and pathological features required to diagnose testicular NK/T-cell lymphoma. In addition, it highlights the dismal survival of these patients. We hope it may serve as a reference aiding prompt clinical diagnosis, which can hopefully improve the survival and quality of life of these patients.